SATRIYA CULTURE AND PUBLIC SERVICE PERFORMANCE: A STUDY OF ORGANIZATION REGIONAL APPARATUS AT THE SPECIAL REGION OF YOGYAKARTA - Kristiawati Tri Utami; Adji Suradji Muhammad (Prodi Ilmu Pemerintahan, Universitas AMIKOM Yogyakarta, 2026)
This study analyzes the implementation of Satriya cultural values by civil servants (ASN) at the Regional Secretariat of the Special Region of Yogyakarta. This study is motivated by the fact that the application of these values still faces challenges, such as differing interpretations among civil servants regarding these cultural values, inadequate implementation of Satriya cultural values by civil servants, obstacles in dissemination, and a lack of consistent monitoring. Based on George C. Edward III’s model, the four main variables of successful implementation are communication, resources, disposition, and bureaucratic structure. Using a qualitative case study approach, data were collected through interviews, observations, and literature reviews, with informants selected through purposive sampling. Values such as harmony, exemplary conduct, and willingness to serve are reflected in ASN’s behavior; however, improving professionalism and service orientation remains challenging. Supporting factors include leadership commitment, organizational structure, and coordination, while inhibiting factors include resource constraints, low discipline, and a work culture not yet fully adaptive. Innovation values are more difficult to internalize than service orientation. This study recommends strengthening synergy between local cultural values and modern bureaucratic systems to achieve good governance.